SMART SPECIALIZATION, ELEMENT OF REGIONAL DEVELOPMENT - Popa, Florina (Studies and Scientific Researches. Economics Edition, 2016)
Research-Development and innovation expenditure (conditions of a few high specializations in different fields of science) know an increasing importance, both at countries level and regions, on the background of challenges that occur in economic growth, at European Union level, involving investment increase in knowledge, respectively, education, professional training, research and development. The existence of a good model of territorial development means finding a strategy and governance able to create new economic activities that capitalize the competitive and comparative advantages of territorial potential, in global context. The new strategy of economic transformation at local level, the smart specialization, aims to promote efficient and effective use of public investment in research, based on innovation encouragement, at regional level, that should lead to economic growth and prosperity of regions. The implementation of strategy`s instruments involves an integrated approach, by using own forces and potential of each region, that should meet the requirements of European Agenda, for growth and competitiveness achievement. By identifying the fields with high potential, at regional level, and their strengthening, the smart specialization can concur to regions access on global markets and international value chain. The study briefly expounds the concept of smart specialization and its constituent sizes, principles of action in the field of research-development and innovation. There are also considered the implementation stages of "strategy", in the interventions at regional level, as well as the advantages and risks that it entails.